The effect of service quality, facilities and environmental cleanliness on tourist satisfaction at the fire flies garden tourist attraction, taro tourism village - Pinaria, Ni Wayan Chintia; Kalpikawati, Ida Ayu; Artajaya, Made; Febrianto, I Gusti Agung (Junal Ilmu Manajemen, 2025)
This study aims to analyze the effect of service quality, facilities, and environmental cleanliness on tourist satisfaction at The Fire Flies Garden. This research uses quantitative and qualitative methods, with primary data obtained through a Likert scale-based questionnaire (1-5) to tourists and interviews with managers. The sampling technique used Accidental Sampling with 60 respondents. Data analysis was conducted using multiple linear regression with the help of SPSS. The results showed that service quality, facilities, and environmental cleanliness have a positive and significant influence on tourist satisfaction, both partially and simultaneously. Tourists are satisfied with the services provided, adequate facilities, and environmental cleanliness that is maintained. The research conclusion confirms that these three variables play an important role in improving the tourist experience and sustainability of tourist destinations.